Perancangan Sistem Kontrol CNC Pengebor PCB Otomatis Berbasis Raspberry PI - Satrio, Eka; Joni, Koko; Wibisono, Kunto Aji (Elektrika, 2021)
Circuit Board (PCB) is a micro-board containing various components electronics used in an automatic circuit. In PCB drilling is usually done human which takes a lot}when the hole in the PCB is getting more and more. And it takes precision when the eye touches the PCB board which gives rise to friction force and can cause drilling. The purpose of this research was the development of tools in the form of automated drills using computers with BCNC software as face-to-face CNC movements. The engine is driven with stepper motor and dc motor as spindle. In this BCNC software the drilling process is done by entering the codes in the form of gcode which can later be read by CNC. The coordinates of the holes in the layout that have been created are obtained by converting the layout into codes called gcode. The process is carried out using PCB designer software. Thoroughness testing on all six axes found an error 1,2% with ten attempts each. PID implementation on DC motor obtained constant value Kp = 54, Ki = 38 and Kd = 0.9. As well as before drilling, the installation of drill bits must be precise so that at the time of spinning, the drill bits do not shake.